Application of a real abandon option with Monte Carlo simulation and conditional volatility GARC: A case study for a mining investment project [Aplicación de una opción real de abandono con simulación Monte Carlo y Volatilidad condicional GARCH: Un caso de estudio para un proyecto de inversión minera] (2017)
In the present work, a study is carried out to determine the financial viability of an investment project in the mining sector, which aims at the extraction of underground gold. In this, the volatility of the gold price is analyzed as a fundamental input, for which the Box Jenkins methodology is used, estimating an econometric model of GARCH volatility. Additionally, the results obtained are contrasted with Monte Carlo simulation. © 2017.